Sweat the small stuff: The human microvasculature and heart disease. (29th September 2020) - Katunaric, Boran; Cohen, Katie E.; Beyer, Andreas M.; Gutterman, David D.; Freed, Julie K.
Abstract: Traditionally thought of primarily as the predominant regulator of myocardial perfusion, it is becoming more accepted that the human coronary microvasculature also exerts a more direct influence on the surrounding myocardium. Coronary microvascular dysfunction (CMD) not only precedes large artery atherosclerosis, but is associated with other cardiovascular diseases such as heart failure with preserved ejection fraction and hypertrophic cardiomyopathy. It is also highly predictive of cardiovascular events in patients with or without atherosclerotic cardiovascular disease. This review focuses on this recent paradigm shift and delves into the clinical consequences of CMD. Concepts of how resistance arterioles contribute to disease will be discussed, highlighting how the microvasculature may serve as a potential target for novel therapies and interventions. Finally, both invasive and non‐invasive methods with which to assess the coronary microvasculature both for diagnostic and risk stratification purposes will be reviewed.